PROFITABILITY MODERATES THE EFFECT OF LEVERAGE, CAPITAL INTENSITY, AND COMPANY SIZE ON EFFECTIVE TAX RATES IN CONSUMER NON-CYCLICALS SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) FOR THE PERIOD 2019-2023 - Hanifah Muzhaffirah; Siti Salamah; Winda Rosa Permatasari; Mohamad Zulman Hakim; Dirvi Surya Abbas; Kimsen (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze and describe empirically the effect of Leverage, Capital Intensity, and Company Size on Effective Tax Rates (ETR) with Profitability as a moderation variable. The population in this study is consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange for the period 2019 – 2023. Sampling was carried out using the purposive sampling method and a final sample of 44 companies was obtained. The analysis method used is moderated regression analysis with the help of Eviews 12. The resultf of F test show that F-value of 2.602340 > 2.41 of the f-value of the table and the Prob(F-statistic) value of 0.000003 < 0.05, it can be concluded that this model is feasible to use. The results of hypothesis test this study show that leverage has a positive effect on effective tax rates, while capital intensity and company size do not show an effect on effective tax rates. In addition, profitability can moderate the effect of leverage on effective tax rates, but it cannot moderate the effect of capital intensity and company size on effective tax rates.